2022
DOI: 10.1111/1365-2656.13823
|View full text |Cite
|
Sign up to set email alerts
|

Host density has limited effects on pathogen invasion, disease‐induced declines and within‐host infection dynamics across a landscape of disease

Abstract: 1. Host density is hypothesized to be a major driver of variability in the responses and outcomes of wildlife populations following pathogen invasion. While the effects of host density on pathogen transmission have been extensively studied, these studies are dominated by theoretical analyses and small‐scale experiments. This focus leads to an incomplete picture regarding how host density drives observed variability in disease outcomes in the field. 2. Here, we leveraged a dataset of hundreds of replicate amphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…The relationship of this species with its NPV appears to be well adapted to variable and increasing environmental warming. Our results support the recent conclusions of Mihaljevic et al (2020) and Wilber et al (2022) that small‐scale transmission studies are unlikely to be sufficient to explain larger‐scale epizootics. Our experiment only used two greenhouses, and while these were very similar in terms of site and conditions, there could have been other, unmeasured factors within each greenhouse that affected the outcome and need to be explored in further studies.…”
Section: Discussionsupporting
confidence: 92%
“…The relationship of this species with its NPV appears to be well adapted to variable and increasing environmental warming. Our results support the recent conclusions of Mihaljevic et al (2020) and Wilber et al (2022) that small‐scale transmission studies are unlikely to be sufficient to explain larger‐scale epizootics. Our experiment only used two greenhouses, and while these were very similar in terms of site and conditions, there could have been other, unmeasured factors within each greenhouse that affected the outcome and need to be explored in further studies.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, we compared frog genomes sampled in 4 populations that have not yet experienced a Bd-caused epizootic ("naive") (45) versus in 5 populations that experienced a Bd epizootic during the past several decades and have since recovered to varying degrees ("recovering"; Figure 5) (14,33). Bd-exposure histories of the 9 study populations are based on 10-20 years of VES and Bd surveillance using skin swabbing (e.g., 14,45,46). Naive populations are characterized by large numbers of adults (i.e, typically 1000s), Bd prevalence that is generally 0% except during occasional Bd failed invasions (during which Bd loads remain very low, 46), and no history of Bd epizootics since we first surveyed these populations in the late 1990s and early 2000s (45).…”
Section: Resultsmentioning
confidence: 99%
“…We also did not directly consider the dynamics of Bd in this model. We made this decision because (i) translocated populations are infected with Bd at high prevalence (41), and (ii) host density does not seem to play a significant role in multi-year Bd infection dynamics in this system (46).…”
Section: Population Viability Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, contrary to theoretical models and small-scale experiments, a recent large-scale study across hundreds of frog populations affected by Bd revealed that population densities only have a very limited influence on real-life disease dynamics and outcomes [47]. Instead, environmental variables such as climatic factors and disease reservoirs were found to be better predictors of amphibian population responses.…”
Section: Discussionmentioning
confidence: 99%